Mathematics teacher educators in the Spanish context: a glance at their beliefs and perceived competence - Giadas, Pablo; Muñiz-Rodríguez, Laura; Rodríguez-Muñiz, Luis J. (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Mathematics Teacher Educators [MTEs] have been a subject of interest in recent years since researchers consider beliefs, and perceived competence to be a fundamental part of MTEs as they affect MTEs’ teaching practice. In this study, a mixed analysis is carried out regarding the beliefs and perceived competence of MTEs in Spain under the theoretical framework of the Mathematics Teacher Educator’s Specialised Knowledge [MTESK] model. Additionally, the relationships between these aspects are examined. The results indicate that some of the MTESK's subdomains rank higher in the MTEs’ relevance. Results exhibit differences regarding MTEs' perceived competence but similar beliefs. Consequently, MTEs could be classified into three clusters based on their perceived competence